[Aleja Piłsudskiego w Gdyni]. - Zdanowski, Edmund (1905-1984) (Gdańsk, 1960)
Przedstawia Aleję Józefa Piłsudskiego w Gdyni, 1960 rok.
Tytuł na rewersie.
Data na rewersie.
Keywords: 1945-1989; 1901-2000; Fotografie; Gdynia (woj. pomorskie)